Conceptual Approaches to the Problem of national Security Concept - Yu. O. Zahumenna (Law and Safety)
A comprehensive theoretical and legal study of the transformation of ideas about the nature of national security reform in domestic jurisprudence has been carried out. The author has defined the priorities and directions of the reform in the field of national security and, more importantly, its theoretical and methodological basis.